1996
DOI: 10.1016/s0741-5214(96)70099-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved method to create the common ostium variant of the distal arteriovenous fistula for enhancing crural prosthetic graft patency

Abstract: Configuration of the adjunctive dAVF may impact on prosthetic graft patency in the crural position. In addition, the type of graft material used for bypass may be instrumental in preventing or precipitating the steal phenomenon. These issues require further study to better understand flow dynamics, patterns of intimal hyperplasia, and blood distribution as a function of conduit material and impedance of the arterial and venous runoff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 16 publications
2
41
1
Order By: Relevance
“…Earlier publications have documented these flow phenomena which have also been confirmed by use of flow meters, angiography, and Doppler sonography. 2,4,11 Most important, however, is the clear improvement in patient symptomatology and limb salvage outcomes. In addition, we have noted a major drop in the number of early postoperative graft failures and need to return to the operating room for thrombectomy and possible graft revision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier publications have documented these flow phenomena which have also been confirmed by use of flow meters, angiography, and Doppler sonography. 2,4,11 Most important, however, is the clear improvement in patient symptomatology and limb salvage outcomes. In addition, we have noted a major drop in the number of early postoperative graft failures and need to return to the operating room for thrombectomy and possible graft revision.…”
Section: Discussionmentioning
confidence: 99%
“…1e3 In addition, 2 variations of the umbilical vein grafts were used during the specific times of their manufacture (Meadox Medicals, 1979e89 and Synovis [BioVascular], 1989e2007) and therefore contribute to the difficulty in creating exact and comparable periods. The current unreported cases (n ¼ 215) added to those cases from prior reports, provide a unique personal experience from which a number of conclusions can be reached 2,4 The number of cases in each period is depicted in Table III and the types of graft materials used and the distribution of the target arteries.…”
Section: Methodsmentioning
confidence: 99%
“…Other authors have reported success for difficult tibial artery bypass with the use of a distal arteriovenous fistula (AVF). [5][6][7][8][9] We extrapolated from this experience to optimize bypass patency in those patients lacking autogenous conduit and disadvantaged arterial runoff by combining the DVP technique with a common ostium AVF.…”
mentioning
confidence: 99%
“…The currently available UV graft is manufactured by BioVascular Inc, Minn. There are available data 7,8 showing absence of aneurysmal degradation with the latter product as well as a significant reduction in the early thrombotic events as documented by Johnson et al 1 with the Meadox product. This is based on improved quality control during manufacture, reduction of residual aldehyde moities in graft and storage media, and appreciation of the surgical skills required for implantation.…”
mentioning
confidence: 99%
“…Additional experience and even better results with the improved UV graft were reported in 1995 7 and 1996. 8 …”
mentioning
confidence: 99%